KAJIAN KUALITAS FISIK DAN KIMIA EFFERVESCENT TEH HITAM (Quality Assessment Of Physical And Chemical on Black Tea Effervescent) (Jurnal Teknologi Pangan, 2015)
Abstract Black tea (black tea/fermented tea) is the result of refined tea leaves and shoots that are experiencing stage of fermentation. The problems that often arise in the making of tea powder is reconstituted at the time of deposition of the occurrence, therefore needs to be added fillers that serve to prevent the deposition of the Dekstrin. The basic formula is Effervescent reaction between the acid with bicarbonate compounds produces carbon dioxide. The purpose of this research was to determine the influence of the addition of Dekstrin and the proportions of citric acid: sodium bicarbonate Effervescent powder Tea against the resulting experimental design in this study using a complete Randomized Design are arranged in a factorial with two factors with 3 times the Deuteronomy The first factor is the addition of Dekstrin (6%, 8%, 10%) and the second factor is the proportion of citric acid: sodium bicarbonate (1: 1; 1: 1.5; 1: 2). The results showed that the best treatment is present on the Effervescent tea with addition of Dekstrin 10% and the proportion of citric acid: sodium bicarbonate 1: 2. The Effervescent produces Moisture 2,3170%, 99,9217%, Solubility Power a Total of 2.56% Acid, Total dissolved solids 9,5180% and 5,2521%, CO2 Levels with a value of organoleptik a sense of 124, scent scum 105,5 110 and appearance   Keyword : effervescent, black tea, dextrine Abstrak Teh hitam (black tea/fermented tea) merupakan hasil olahan pucuk daun teh yang mengalami tahap fermentasi. Permasalahan yang sering timbul pada pembuatan bubuk teh adalah terjadinya pengendapan pada saat dilarutkan, oleh karena itu perlu ditambahkan bahan pengisi yang berfungsi untuk mencegah pengendapan yaitu Dekstrin. Dasar formula Effervescent adalah reaksi antara senyawa asam dengan bikarbonat menghasilkan karbondioksida. Tujuan dari penelitian ini untuk mengetahui pengaruh penambahan Dekstrin dan proporsi Asam Sitrat : Natrium Bikarbonat terhadap serbuk Effervescent Teh yang dihasilkan Rancangan percobaan dalam penelitian ini menggunakan Rancangan Acak Lengkap (RAL) yang disusun secara faktorial dengan dua faktor dengan 3 kali ulangan. Faktor pertama adalah penambahan Dekstrin (6%, 8%, 10%) dan faktor kedua adalah proporsi Asam Sitrat : Natrium Bikarbonat ( 1:1 ; 1:1,5 ; 1:2).   Kata kunci : efervesen, teh hitam, dekstrin